An Energy Efficient Anchor-Free Localization Algorithm for No-Identity Wireless Sensor Networks. (9th December 2015) - Qu, Zhe; Shu, Minglei; Yang, Ming; Zhang, Chongqing; Wei, Nuo; Guo, Qingbei; Du, Tao
Abstract : A wireless sensor network (WSN) model by analyzing the limitations of existing localization algorithm is proposed in this paper. Specifically, neither the anchor nor the ID is required in the proposed model, and the node function is limited. The hardware function of the node in our model is independent of the MAC protocol. Moreover, based on the proposed WSN model, we design an energy efficient anchor-free localization algorithm for no-identity WSN. Instead of multiple measurements, mathematical calculation is adopted to acquire the position information. Subsequently, the effectiveness of the algorithm is confirmed by rigid theory. The simulation results show that the proposed algorithm can improve the performance of localization and energy efficiency in WSN significantly.